2007
DOI: 10.1097/brs.0b013e318067dd72
|View full text |Cite
|
Sign up to set email alerts
|

2006 Young Investigator Award Winner: Lumbosacral Nerve Root Displacement and Strain

Abstract: Prepositions of the SLR test alter the displacement and possibly the strain of the lumbosacral nerve roots in the lateral recess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…Previous research has demonstrated that the amount of inherent tension to which a peripheral nerve is exposed can have a direct influence on the amount of nerve excursion available when the limb moves 1 4 . Although nerve tension was not quantified, the results of the current study suggest that the assumed increase in generalised neural tension applied to the spinal cord and lumbo-sacral nerve roots by slump-sitting did not alter sciatic nerve excursion.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Previous research has demonstrated that the amount of inherent tension to which a peripheral nerve is exposed can have a direct influence on the amount of nerve excursion available when the limb moves 1 4 . Although nerve tension was not quantified, the results of the current study suggest that the assumed increase in generalised neural tension applied to the spinal cord and lumbo-sacral nerve roots by slump-sitting did not alter sciatic nerve excursion.…”
Section: Discussioncontrasting
confidence: 45%
“…However, the argument for anatomic distance and relative neural tension is controversial. From their cadaver based research, Gilbert et al 1 concluded that the addition of ankle dorsiflexion to the SLR caused a significant decrease in displacement of the L5 and S1 nerve roots. In regard to nerve root strain, it was evident that ankle dorsiflexion resulted in greater strain, however this did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Last, a study using 5 unembalmed cadavers (age range, 72-88 years) found that ankle mobility was limited to between -5° and 5° of dorsiflexion without cutting the calcaneal tendon. 9,10 These findings suggest that the limitations in hip and ankle ranges of motion found in the present study are likely due to age-related changes in this specific sample. Despite the limited range of motion, the maximal increase in strain that was observed in our study (7% at the hip and ankle) is representative of maximal increases in nerve strain when using fresh or unembalmed cadavers.…”
Section: Discussionmentioning
confidence: 46%
“…While not measured, we do not believe that hamstring extensibility was significantly affected by changes in the displacement or strain of the lumbosacral nerve roots during iSLR testing. By stabilizing the lumbar spine and using a fixed ankle position we have controlled these potentially confounding variables that have been observed to increase spinal nerve root tension [32]. Finally, the two measures of passive stiffness were based on the slope through the common range of motion (20 to 50° hip flexion) and the maximal applied torque.…”
Section: Discussionmentioning
confidence: 99%